Coronary Artery Bypass Grafting using Bilateral Internal Thoracic Arteries through a Left-Sided Minithoracotomy: A Single-Center Starting Experience - Diab, Mahmoud; Färber, Gloria; Sponholz, Christoph; Tasar, Raphael; Lehmann, Thomas; Tkebuchava, Sophie; Franz, Marcus; Doenst, Torsten (The Thoracic and Cardiovascular Surgeon, 2019)
Background Coronary artery bypass grafting (CABG) using bilateral internal thoracic artery (BITA) is associated with the best long-term survival. However, using BITA increases the risk of sternal wound infections with conventional sternotomy. We describe here our initial results of minimally invasive CABG (MICS-CABG) using BITA.Methods Patients were operated through an incision similar to that of standard minimally invasive direct CABG. All operations were performed off-pump. We evaluated patient's quality of life (QoL) using the Medical Outcomes trust, 36-Item Short Form Health Survey (SF-36).Results Between February 2016 and August 2017, we performed 21 cases of MICS-CABG using BITA. There was no intraoperative complication and no conversion to sternotomy or to on-pump. Two patients required reexploration through the same minithoracotomy for postoperative bleeding. Two cases of early postoperative graft failure were identified. There was no stroke or in-hospital mortality. The median duration of follow-up was 13 months, with a maximum of 19 months. Relief of angina was achieved in all patients. There was one readmission for superficial wound infection, which was conservatively treated. An 84-year-old man died 4 months after the operation. The remaining 20 patients attested good QoL with the SF-36 questionnaire.Conclusions Myocardial revascularization using BITA can be safely achieved off-pump through a left-sided minithoracotomy with good postoperative and short-term outcomes.
Keywords: coronary artery bypass grafting; bilateral internal thoracic arteries; minimally invasive; mortality